Method comparison of Particle Enhanced Immunoturbidimetry (PEIT) with High Performance Liquid Chromatography (HPLC) for glycated hemoglobin (HbA1c) analysis - Shabnam Dildar; Sheharbano Imran; Farah Naz (Clinical Diabetes and Endocrinology, 2021)
Abstract Background and objective High Performance Liquid Chromatography (HPLC) technique is considered as a gold standard for HbA1c analysis however all laboratories cannot adopt it due to certain limitations. Our aim was to compare Particle Enhanced Immunoturbidimetry (PEIT) method with High Performance Liquid Chromatography (HPLC) for HbA1c analysis. Method All blood samples were analyzed by HPLC assay on a Bio-Rad D-10 analyzer and PEIT on an Erba XL-200 analyzer. Precision studies were undertaken and Coefficient of Variation (%CV) calculated. Systemic Error (SE), Random Error (RE) and Total Error (TEcalc) were obtained. The Total Allowable Error (TEa) set by the National Glycohemoglobin Standardization Program (NGSP) for HbA1c is 6%.The acceptable evaluation method is where TEcalc is less than TEa. Results The Precision studies were satisfactory with Coefficient of Variation (%CV) being less than 4% for both techniques. Mean HbA1c levels were slightly higher from HPLC than PEIT 9.07 ± 2.23% and 8.93 ± 2.10% respectively, although the difference was minimal. RE was 1.41%, TEcalc was 1.55%, which was less than TEa set by the NGSP. Both methods strongly correlated with the correlation coefficient (r) 0.9716, p < 0.0001. Conclusion Our study showed HbA1c analysis by PEIT technique is precise, accurate, rapid and convenient and can be employed as an alternative to HPLC technique in countries where cost is a major problem for diagnosis and treatment.